Goods to Good: Effect of Thai Consumers’ Awareness of Corporate Social Innovation (CSI) on the Innovation Adoption Factors, Predictors of Behavioral Intention, and Brand Purchase Intention - Kaitkanarat, Sora; Kesaprakorn, Pacharaporn; Komolsevin, Rosechongporn; Punnahitanond, Ratanasuda (Executive Journal, 2020)
This study examined the impact of Corporate Social Innovation (CSI) on the innovation adoption factors (perceived relative advantage (RA) and perceived compatibility (CP)), predictors of behavioral intention (subjective norm (SN), attitude (AT), and perceived behavioral control (BC)), and their purchase intention (PI) among Thai consumers. A total of 480 Bangkok residents aged between 25 to 40 years old were randomly selected. The results through Partial Least Square-Structural Equation Model (PLS-SEM) analysis with a significance level of 0.05 revealed six findings: (1) The awareness of CSI directly influenced the innovation adoption factors (RA and CP), predictors of behavioral intention (SN, AT, and BC), but not on purchase intention, (2) the awareness of CSI indirectly affected purchase intention, as mediated by each of the predictors of behavioral intention (SN, AT, and BC) and as mediated by brand loyalty together with perceived relative advantage, (3) the innovation adoption factors (RA) and attitude directly affected brand equity (perceived quality (Q) and brand loyalty (L)), (4) brand equity (Q) influenced attitude directly, (5) subjective norm and perceived behavioral control directly affected attitude, and (6) all predictors of behavioral intention (SN, AT, and BC) significantly influenced the purchase intention. The results of this CSI study fill the gap in the body of knowledge, and at the same time, create a potential framework for an organization to adopt this CSI practice for the sustainable betterment of both organization and society as a whole.